Aggressive Environment Resistance of Concrete Products Modified With Nano Alumina and Nano Silica - Zhao, Yao; Cui, Na; Zhao, Shuyuan; Zhu, Yunzhe; Hou, Pengkun; Feng, Lichao; Xie, Ning (Frontiers in Materials, 2021)
The service life of concrete products with exposure to an aggressive environment has raised great concerns in the past decades. Nanomaterials have been used as a promising approach to improve the environmental resistance of concrete products when exposed to synergistic attacks. The impacts of CaCl2 on nano-modified concrete, especially along with freeze/thaw (F/T) and wet/dry (W/D) cycles, were barely discussed. In this study, the impacts of CaCl2 along with F/T and W/D cycles on the nano SiO2 and Al2O3 modified concrete were investigated. The mass loss, flexural strength, compressive strength, and relative dynamic modulus of elasticity were tested to evaluate the durability of concrete products. The testing results indicate that the addition of nanoparticles has a distinctive effect on the environment resistance enhancement of concrete samples. The microstructure analysis demonstrates that with the addition of nanoparticles, high-density hydration products were formed, which is beneficial to the properties enhancement of concrete products. This study not only provides an approach to realize the nano modification on the durability of concrete products but also helps to design and fabricate environmentally resistant concrete products when exposed to a synergistic aggressive environment.